2005
DOI: 10.1016/j.trstmh.2004.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Plasmodium falciparum genotypes in clinically mild and severe malaria cases in Orissa, India

Abstract: A cross-sectional study was conducted in a malaria hyperendemic state of India to ascertain the distribution of Plasmodium falciparum genotypes in patients with mild (n=40) and severe (n=35) malaria. PCR and nested PCR were used to determine the glutamate-rich protein (GLURP), merozoite surface proteins 1 and 2 (MSP1 and MSP2) and knob-associated histidine-rich protein (KAHRP) for characterization of the parasite. The results indicate that (i) the 200bp allele of the MAD20 family of MSP1 and the 550bp allele o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
40
2
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 26 publications
9
40
2
4
Order By: Relevance
“…Therefore, an insight in the genetic structure of these populations is necessary to develop strategies to control the disease, including the design of effective vaccines against P. falciparum. Our results reveal a diverse nature of P. falciparum isolates of malarious districts of Jharkhand in respect of length as well as sequence motifs with prevalence of all the allelic families of msp-1 and msp-2 which are in agreement with the earlier reports from different regions on Indian Isolates (Raj et al, 2004;Ranjit et al, 2005;Joshi et al, 2007). Despite of substantial regional variations, recent increases in P. falciparum incidence and malaria-associated death, Jharkhand represents a low malaria transmission setting with mesoendimicity (Hamer et al, 2009;Dhingra et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, an insight in the genetic structure of these populations is necessary to develop strategies to control the disease, including the design of effective vaccines against P. falciparum. Our results reveal a diverse nature of P. falciparum isolates of malarious districts of Jharkhand in respect of length as well as sequence motifs with prevalence of all the allelic families of msp-1 and msp-2 which are in agreement with the earlier reports from different regions on Indian Isolates (Raj et al, 2004;Ranjit et al, 2005;Joshi et al, 2007). Despite of substantial regional variations, recent increases in P. falciparum incidence and malaria-associated death, Jharkhand represents a low malaria transmission setting with mesoendimicity (Hamer et al, 2009;Dhingra et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…MAD20 is observed to be predominant allele in the P. falciparum population in Jharkhand, which is consistent with the situations in Thailand, Iran, Pakistan and Colombia Gmez et al, 2002;Zakeri et al, 2005;Ghanchi et al, 2010). Interestingly, the prevalence of K1zMAD20 mixed genotype in India 586 (Ranjit et al, 2005), and in the present study is substantially higher than what was observed in Pakistan by Khatoon et al (2010). On the other hand, MSP-2 in both 3D7 and FC27 allele types were identified among the isolates from Jharkhand.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, fewer genotypes, have adhered to CD36 (P = 0.01) in severe malaria in comparison with uncomplicated cases. In endemic areas the association of complexity of infections with the severity of attack was conflicting, as some authors found a lower complexity in severe malaria (Robert et al, 1996) while others claimed opposite results (Mockenhaupt et al, 2003;Ranjit et al, 2005). This present work allowed validating our methodology.…”
Section: Discussionmentioning
confidence: 52%
“…Interestingly, another recent study by the Rogerson's group suggested that the dominant clones sequestered in deep organ during severe malaria are usually the same as those in peripheral circulation (Dembo et al, 2006), which supports continued experimental work using circulating parasites. Several studies have used merozoites surface proteins (msp-1 and/or msp-2) polymorphism to describe circulating parasite populations and some authors reported the association of particular genotypes with severity of malaria attack (Ariey et al, 2001;Mockenhaupt et al, 2003;Ranjit et al, 2005;Farooq et al, 2006). However, these associations were described as possibly restricted to geographical areas.…”
Section: Discussionmentioning
confidence: 99%
“…23 By contrast, in Nigeria it has been shown that the presence of the K1 and MAD20 alleles was significantly associated with asymptomatic malaria, and consequently, a reduced risk of developing the symptomatic disease. 34 Ranjit et al 35 have also shown that Mad20/MSP-1 and 3D7/MSP-2 alleles were over-represented in severe malaria cases in Orissa (India). Finally, it has also been reported that clinical malaria was associated with 3D7/MSP-2 in some African endemic areas.…”
Section: Discussionmentioning
confidence: 97%